Penentuan Tipe Inhibisi Senyawa Analog Kurkumin CA2 terhadap Enzim α-Glukosidase dari Beras Lapuk - Atiqoh Zummah; Endang Astuti; Bambang Purwono (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
Diabetes is a health problem that exists throughout the world, especially in Indonesia. Based on data compiled from the International Diabetes Federation (IDF) in 2017, people with diabetes in Indonesia reached 10.3 million people, and if not handled properly it is suspected that there will be an increase to 21.3 million people in 2030. Curcumin analog compounds can used for the treatment of diabetes by inhibiting the enzyme α-glucosidase. The curcumin analog compound used in this study was synthesized from 4 methoxybenzaldehyde with cyclopentanone which was then called the CA2 compound. The α-glucosidase enzyme used in this study was obtained through extraction of weathered rice with an optimum pH of 4.5 and the enzyme extract fraction used was fraction II which had the highest activity compared to fractions I and III. The results showed that the values of the kinetic parameters Km and Vmax of the extracted α-glucosidase enzyme were 1.53 mM and 0.03 U/mL, respectively. The Km kinetic parameter value changed to 1.66 Mm while the Vmax value did not change when the α-glucosidase enzyme was inhibited by CA2 compound, so that the type of inhibition shown by CA2 compound was competitive.